A co-produced teaching experience to promote nursing students’ care and compassion towards mental health service users - Davenport, Caroline; O'Brien, Samantha (University of Hull, 2025)
This blog describes a teaching session we co-produced and delivered to around 300 second year student nurses. We recently followed it up by publishing an article reflecting on the experience (O’Brien and Davenport, 2024) and highlighting the need for a co-produced nursing curriculum.